2014
DOI: 10.1080/09291016.2014.921409
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of cognitive performance and perceived difficulty in dart-throwing performance in 9–10-year-old boys

Abstract: The aim of this study was to investigate variations in cognitive performance and difficulty perception in 9-10-year-old boys. Fifteen healthy boys (Age = 9.8 ± 0.4 years; Height = 146 ± 5.2 cm; Body mass = 34.2 ± 2.9 kg) performed three cognitive tasks, the reaction time (RT), the trail-making test, TMT (to evaluate flexibility), and the barrage tests (to evaluate selective attention [SA]). The tests were performed at 07:00 and 17:00 h. The results demonstrated that oral temperature, RT, and flexibility were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
0
12
1
Order By: Relevance
“…Participants then participated in three experimental trials in a randomized manner at the same time of day (07:00 h), separated at least by five days. The three trials consisted of a no-walking session (no-WS: Control session (CS)) (Subjects performed a dart-throwing test and cognitive tasks) 15 and two 15-min walking sessions (WS), with each WS trial performed at a different intensity as reported by 4 . After each WS subjects performed a dart-throwing test in two experimental sessions and cognitive tasks.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Participants then participated in three experimental trials in a randomized manner at the same time of day (07:00 h), separated at least by five days. The three trials consisted of a no-walking session (no-WS: Control session (CS)) (Subjects performed a dart-throwing test and cognitive tasks) 15 and two 15-min walking sessions (WS), with each WS trial performed at a different intensity as reported by 4 . After each WS subjects performed a dart-throwing test in two experimental sessions and cognitive tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The first distance was 2 m (SD); the second was at the regular distance of 2.37 m (LD). The two distances were marked by a line on the floor 15 . After each session, a questionnaire to asses PD (DP-15) was completed by the subjects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations